Historical facts about the Mamluk period in the novel of the Egyptian writer Salah Maaty - Aubakyrova, K. K. (Journal of Oriental Studies, 2016)
the article considers contemporary egyptian writer salah Maaty’s novel "hizanat shamail" and historical events which have found reflection in his novel.